2017
DOI: 10.1016/j.neuron.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Selective Optogenetic Control of Purkinje Cells in Monkey Cerebellum

Abstract: SUMMARY Purkinje cells of the primate cerebellum play critical but poorly understood roles in the execution of coordinated, accurate movements. Elucidating these roles has been hampered by a lack of techniques for manipulating spiking activity in these cells selectively—a problem common to most cell types in non-transgenic animals. To overcome this obstacle, we constructed AAV vectors carrying the channelrhodopsin-2 (ChR2) gene under the control of a 1 kb L7/Pcp2 promoter. We injected these vectors into the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 116 publications
1
69
0
Order By: Relevance
“…Optogenetic applications in NHPs have facilitated our understanding of sensory processing, decision making, and the bases of cognition 11,12,16,21,37 , and will likely play a key role in future brain-computer-interfaces, neural prosthetics, and methods to counteract cognitive decline in the aging human brain. As such, optogenetic techniques are undergoing rapid translation to human clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optogenetic applications in NHPs have facilitated our understanding of sensory processing, decision making, and the bases of cognition 11,12,16,21,37 , and will likely play a key role in future brain-computer-interfaces, neural prosthetics, and methods to counteract cognitive decline in the aging human brain. As such, optogenetic techniques are undergoing rapid translation to human clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Cortex. Channelrhodopsin-2 (ChR2) is a commonly used optogenetic actuator for NHPs, though it often requires high laser power to evoke neuronal and behavioral responses [14][15][16][17]21 . The high conductance and red-shifted absorption spectrum of C1V1 makes it a preferable choice 12,34,38,39 .…”
Section: Expression Of Optogenetic Actuator and Calcium Indicator In mentioning
confidence: 99%
See 1 more Smart Citation
“…This is the scale at which electrical microstimulation has proven most effective, but primate systems neuroscience has lacked an inactivation counterpart with comparable spatial and temporal specificity, relying instead on pharmacological and cooling methods that last minutes to days and affect larger swaths of tissue. There is understandable excitement surrounding the development of optogenetic methods for targeting particular cell types or projections (El-Shamayleh et al, 2017;Klein et al, 2016;Stauffer et al, 2016;Ohayon & DiCarlo, Soc. Neurosci.…”
Section: Focal Optogenetic Suppressionmentioning
confidence: 99%
“…Indeed, even the development of optogenetic techniques for NHPs in the central nervous system (CNS) has proven challenging with examples of successful viral transduction studies slowly beginning to accumulate [27][28][29][30][31][32][33]. A handful of studies have demonstrated viral transduction of peripheral neuromuscular tissue with fluorescent proteins in NHP models [34,35], but optogenetic modulation of peripheral neural activity in primates similar to the aforementioned rodent studies has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%